Analisis Usaha Peternakan Ayam Petelur di Kecamatan Adiluwih, Pringsewu - Fitriani Fitriani (Jurnal Ilmiah ESAI, 2015)
The situation of cost production and price are influenced by the success of lying hen business. This study conducted to analyze the cost of production, revenue, and income at small scale lying hen business in Adiluwih Subdistrict of Pringsewu. Ten small scale lying hen businesses at Adiluwih Sub district were taken as the respondents of study. The cost and revenue analysis, as well as the R/C and B/C ratio were applied to solve the problem.  Based on the fact revealed, the lying hen at productive phase was profitable.  The benefit was bigger than the cost (B/C= 0,198).   The net income per month was higher than the minimum regional wage. It reaches almost IDR 5 million per month. It means that lying hen business could be the main household income. The challenge was the cash flow management to minimize the risk.  The cash out flows for feed were unstable, too high and need huge fund.  The cash-in flows were also not secure as it depends on the price and trader payment.  The ability of risk management was a key to guarantee the success of lying hen business in the future.  Key words: lying hen, production cost, revenue, income